1991
DOI: 10.1038/bjc.1991.20
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of body fat composition with sterculic acid can inhibit mammary carcinomas in vivo

Abstract: Summary Sterculic acid, a A-9-desaturase inhibitor, administered to rats caused a rise in the stearic:oleic acid ratio of total lipids in peripheral red cells, serum and liver (P <0.001). As a reduction in the stearic:oleic acid ratio has been described in cancer cells, we investigated the effect of sterculic acid on tumour growth. Female F344 rats were injected subcutaneously with two different doses of sterculic acid for 4 weeks prior to, and 4 weeks following, implantation of a nitrosomethylurea-induced mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 26 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Several treatments or conditions that are associated with hepatocarcinogenesis (57, 59) also increase SCD1 expression, and SCD1 levels are higher in rat mammary carcinomas (60) and in mice that are genetically susceptible to hepatocarcinogenesis (61). Sterculic acid, an inhibitor of SCD1 activity, blocks rat mammary carcinogenesis (62). In our study, the increased SREBP1c expression observed in AlbCrePten flox/flox mice may have induced SCD1 upregulation and an accumulation of monounsaturated fatty acids that may have promoted hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 65%
“…Several treatments or conditions that are associated with hepatocarcinogenesis (57, 59) also increase SCD1 expression, and SCD1 levels are higher in rat mammary carcinomas (60) and in mice that are genetically susceptible to hepatocarcinogenesis (61). Sterculic acid, an inhibitor of SCD1 activity, blocks rat mammary carcinogenesis (62). In our study, the increased SREBP1c expression observed in AlbCrePten flox/flox mice may have induced SCD1 upregulation and an accumulation of monounsaturated fatty acids that may have promoted hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the proportional enrichment of phospholipids with SFA promotes cytostatic effects in cancer cells (39). Furthermore, sterculic acid, an inhibitor of SCD activity, exhibits an anti-proliferative action in neoplastic cells likely by increasing the relative abundance of SFAs (40). Finally, the inhibition of fatty acid synthesis observed in SCDdepleted cells may be also responsible for the decrease in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Sterculic acid also can inhibit mammary carcinoma growth in rats (Khoo et al, 1991). In our previous work (Sun and Li, 2016), we found that Phoenix tree seed oil is rich in sterculic acid (S, 23.2%).…”
Section: Introductionmentioning
confidence: 99%